Radioactivity in building materials and assessment of risk of human exposure in the East Khasi Hills District, Meghalaya, India. Issue 1 (1st January 2020) - Lyngkhoi, B.; Nongkynrih, P.
ABSTRACT: Gamma-ray spectrometer was employed to estimate the specific activity of the natural radionuclides in commonly used building materials of East Khasi Hills District, Meghalaya, India. The activities of 40 K, 226 Ra and 232 Th in Bq kg −1 were 40.9–777.1, 3.8–92.7 and 14.2–112.2 with their total average values of 312.4, 47.4 and 57.7, respectively. 40 K and 226 Ra concentrations were below the reported values of 500 Bq kg −1 and 50 Bq kg −1, respectively, while 232 Th was slightly higher than 50 Bq kg −1 . The average annual effective dose (outdoor) of 0.09 mSv y −1 was much lower than the recommended limit of 1 mSv y −1 for public exposure; absorbed dose rate (69.9 nGy h −1 ) was higher than the world average value of 59 nGy h −1 . The average values of radium equivalent activity (154.0 Bq kg −1 ), alpha index (0.24), gamma index (0.55), external hazard index (0.42) and internal hazard index (0.54) were all less than the recommended values. Our study shows that the different types of building materials analyzed do not pose any significant radiation hazards. They are therefore safe for the construction purposes. The statistical methods applied in our study show that 40 K contributed less to the values of the radiological parameters compared to 226 Ra and 232 Th.